Congenital syphilis: performance of primary care services in São Paulo, 2017 - Couto, Caroline Eliane [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP]; Sanine, Patrìcia Rodrigues [UNESP]; Mendonça, Carolina Siqueira [UNESP]; Nunes, Luceime Olìvia [UNESP]; Zarili, Thais Fernanda Tortorelli; Dias, Adriano [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
OBJECTIVE: To evaluate congenital syphilis prevention actions in primary health care services in the state of São Paulo. METHODS: Cross-sectional evaluative research that used indicators extracted from the Survey of Evaluation and Monitoring of Primary Care Services (Avaliação e Monitoramento de Serviços da Atenção Básica — QualiAB) in the state of São Paulo in 2017. An evaluative matrix composed of 31 indicators of prevention of congenital syphilis, categorized into four domains of analysis: diagnosis and treatment of acquired syphilis (10); basic infrastructure and resources (7); prevention of congenital syphilis during prenatal care (7); and educational actions and prevention of sexually transmitted infections (7). The frequency of services with positive responses for each indicator and the percentage of service performance were calculated based on the proportion of indicators reported per service and the overall average observed. Subsequently, services were classified into four quality groups, and associations between groups and each indicator, type of organizational arrangement and location were estimated. RESULTS: 2,565 services participated, located in 503 municipalities, with an overall average performance of 74.9%. The domain “diagnosis and treatment of acquired syphilis” had the highest performance (89.8%), followed by “infrastructure and basic resources” (79.5%), “prevention of congenital syphilis in prenatal care” (73.3%) and “educational actions and prevention of sexually transmitted infections” (56.8%). There was a significant difference between quality groups and all indicators and types of organizational arrangements. CONCLUSIONS: The evaluated services have limitations in the development of actions to prevent congenital syphilis, mainly related to health education and actions included in prenatal care, such as screening and adequate treatment of pregnant women and their partners. Changes are needed in the work process, with the expansion of educational and surveillance actions, as well as the qualification of the teams to effectively comply with the protocols.
Keywords: Congenital; Disease Prevention; Health Services Research; Primary Health Care; Surveys and Questionnaires; Syphilis